CFD modelling of aerodynamic sealing by vertical and horizontal air curtains - Goncalves, J.C. (2012)
This work presents a comparative study of the aerodynamic sealing of doorways of refrigerated rooms, obtained by vertical and horizontal air curtain devices (ACD). The sealing efficiency is estimated for different situations, with the ACD installed inside, outside or on both sides of the door. For this purpose, a numerical model was developed for the simulation of the turbulent non-isothermal 3D airflow generated by the air curtain in the transient period after the door is opened. The buoyancyinduced airflow field when the ACD is turned off and the door is open was taken as a reference to assess the sealing efficiency. Numerical results are plausible and comply with the physical interpretation of the convective phenomena. In line with previous investigations, the optimum velocity of the air jet was found, corresponding to the highest sealing effect. The advantage of installing the ACD outside the refrigerated room was shown by the present simulations. According to the present study, downward blowing air curtains present better sealing efficiency (over 70%) compared to horizontal jet air curtains (about 55%). Although the direct air recirculation provides a better sealing efficiency (over 80%), the system complexity and the installation and maintenance costs inhibit its common use.